PENINGKATAN SKILL EDITING FOTO & VIDEO MELALUI PELATIHAN PENGENALAN APLIKASI EDITING PADA SISWA KELAS X - Muflikhun, Muhammad Naufal; Febrianto, Rian; Syailendra, Dwimas; Wibawa, Bimantara Bakti; Setiawan, Aria Nanda; Rahmah, Hilda (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
The increasing demand from companies and the need for job vacancies in the field of photo and video editing in the media today has made it urgent for students majoring in broadcasting to hone their editing skills before jumping in and getting involved in the media industry. Based on observations, the limited human resources available in schools often prevent students from realizing the importance of these skills, so in order to accelerate knowledge, cooperation, and participation of students is needed to improve photo and video editing skills beyond those provided by the school. This community service aims to improve photo and video editing skills through training in the introduction of Adobe Photoshop and Adobe Premiere editing applications, for class X students majoring in Broadcasting at SMKN 1 Demak. The method used in this activity is Participatory Action Research (PAR), with stages, namely, observation, planning, action, and evaluation. The training includes an introduction to several photo and video editing applications, Adobe Photoshop and Adobe Premiere, as well as effective editing techniques. The results of this activity obtained a percentage increase in knowledge about photo and video editing skills of 82.7%. High student enthusiasm also shows an increase in theoretical understanding of how to edit photos and videos. This training has helped students apply photo and video editing skills in terms of promotions, digital marketing, company profiles, and personal branding of a product. Furthermore, this skill also opens up opportunities for students to be able to create businesses independently in the field of creating strategies and creative content.